Activated prothrombin complex concentrate (APCC)‐mediated activation of factor (F)VIII in mixtures of FVIII and APCC enhances hemostatic effectiveness. Issue 5 (15th May 2013) - Yada, K.; Nogami, K.; Ogiwara, K.; Shima, M.
Summary: Background and objectives: Activated prothrombin complex concentrates (APCCs), utilized in bypassing therapy for hemophiliacs with inhibitor, contain factors (Fs) VII, FII, FIX and FX, and their active forms. A recent report has demonstrated that mixtures of APCC and FVIII potentiated thrombin generation, in vitro, in plasma from patients with severe hemophilia A, but the mechanism(s) involved remains unknown. Results: APCC (0.05 U mL −1 ) increased FVIII activity ~ 4‐fold within 1 min in one‐stage clotting assays, followed by a return to initial levels within 10 min. This reaction was dependent on the presence of tissue factor and phospholipid. Thrombin generation produced from APCC was ~ 3.5‐fold greater in the presence of FVIII than that in its absence. SDS‐PAGE analysis revealed that APCC sequentially proteolyzed the heavy chain of FVIII at Arg 372 and Arg 740, followed by cleavage at Arg 336 . Proteolysis was prevented by FVIIa inhibitor, but not by hirudin, supporting the concept that APCC itself possessed the potential to activate FVIII in early coagulation phases, and that FVIIa in APCC contributed mainly to this reaction. APCC‐mediated FVIII activation was unaffected by the addition of anti‐FVIII inhibitor antibodies, irrespective of epitope specificity. Anti‐C2 type 1 inhibitors, however, diminished the inactivation phase of the APCC reaction by inhibiting cleavage at Arg 336 . Conclusion: Small amounts of APCC, relative to the standard concentration used for clinical purposes, could activate FVIII directly, even in the presence of anti‐FVIII antibodies. Combination therapy based on mixtures of APCC and FVIII could have significant beneficial implications for the treatment of hemophilia A patients with inhibitors.